Topical Liposomes: A Paradigm Shift on Topical Delivery of Drugs: Pharmaceutical Science-Pharmacy - Rashid Iqbal, Mohammad (International Journal of Life Science and Pharma Research, 2022)
Abstract: A micro hydrodynamic focusing (MHF) technique, first suggested by Jahn et al., has successfully created monodisperse liposomes utilizing microfluidic technology. Because of their particular features, liposomes are used for medicine delivery. Indeed, they can include a wide range of hydrophilic and hydrophobic diagnostic or therapeutic agents, allowing for a greater drug payload per particle while also shielding the encapsulated compounds from metabolic processes. Many basic sciences have proven liposomes to be a promising new medication delivery method. Liposomes are tiny spheres of aqueous core and one or more lipidbased outer shells organized in a bilayer pattern. The ability to encapsulate hydrophilic and lipophilic medications and shield them from deterioration makes liposomes acceptable as better carriers. It can penetrate deeper into the skin and, as a result, provide higher absorption. It also has an affinity for the keratin of the horny layer of skin. When applied to the skin, liposomes may function as a local depot, a matrix for solubilizing poorly soluble medicines, and an enhancer of penetration while reducing their negative effects. Due to their adaptability and clinical efficacy, liposomal formulations are frequently employed in the pharmaceutical industry as drug delivery systems. They have been used to distribute medications via several routes, including oral, parenteral, and topical. Among these, topical delivery of drugs carried by liposomes exhibits interesting applications, not only for enhancing transdermal delivery of drugs intended for systemic use, thus more effectively utilizing this noninvasive alternative route to oral administration, but also for promoting dermal delivery of drugs which have to act topically, such as local anaesthetics. Topical liposome formulations have the potential to be less harmful and more effective than standard formulations. The extended and controlled release of the topical dosage forms used in liposome gel formulations may increase efficacy and patient compliance while producing therapeutically superior effects compared to standard formulations.